Development of Worksheet Based on Assessment for Learning (AfL) to Improve Problem Solving Skills on Acid-Base Material - Tiana, Merynke Ayu Nava; Muchlis, Muchlis (Hydrogen: Jurnal Kependidikan Kimia, 2025)
The purpose of this study is to ascertain how well Assessment for Learning (AfL)-based learner worksheets enhance students' ability to solve problems involving acid and base materials, particularly salt hydrolysis sub-materials. This study is a development study that is restricted to the develop stage and uses a 4D model. The research subjects were XII grade students at SMAN 14 Surabaya. The research instruments consisted of validation sheets, pre-test, and post-test of problem solving skills. Validation was conducted by 3 expert validators with the results showing that the worksheet met the valid criteria in terms of content, construct, and graphics. Limited trials were conducted in two meetings using two worksheets. The results of the Wilcoxon test revealed a significant difference between the pre-test and post-test, with a significance value of 0.000 (p < 0.05). According to the N-Gain analysis, there were five pupils in the low group, eleven in the medium category, and fourteen in the high category. According to these findings, students' problem-solving abilities are effectively enhanced by the AfL-based worksheets. Through a contextual approach and group discussions, this worksheet effectively combines Polya's problem solving paradigm with the stages of AfL.